Effects of testosterone replacement therapy on metabolic syndrome among Japanese hypogonadal men: A subanalysis of a prospective randomised controlled trial (EARTH study). (12th May 2017) - Shigehara, K.; Konaka, H.; Nohara, T.; Izumi, K.; Kitagawa, Y.; Kadono, Y.; Iwamoto, T.; Koh, E.; Mizokami, A.; Namiki, M.
Summary: We investigated the effects of testosterone replacement therapy (TRT) on metabolic factors among hypogonadal men with a metabolic syndrome. From the study population of the EARTH study, which was a randomised controlled study in Japan, 65 hypogonadal patients with a metabolic syndrome, comprising the TRT group ( n  = 32) and controls ( n  = 33), were included in this study analysis. The TRT group was administered 250 mg of testosterone enanthate as an intramuscular injection every 4 weeks for 12 months. Waist circumference, body mass index, body fat volume and blood pressure were measured in all patients at baseline and at 12 months. In addition, blood biochemical data, including total cholesterol, triglyceride (TG), HDL cholesterol, fasting plasma glucose (FPG) and haemoglobin A1c (HbA1c) levels, were also evaluated. Changes in these categories from baseline to 12 months were compared between the TRT and control groups, with significant differences observed in waist circumference, body fat percentage, FPG, TG and HbA1c levels. No significant differences were observed in other parameters. TRT for 1 year was associated with improvements in some metabolic factors among Japanese men with hypogonadism and metabolic syndrome.